The relationship between office environment and job satisfaction among employees at Majlis Agama Islam dan Adat Istiadat Melayu Kelantan (MAIK) / Faras Fauzi - Fauzi, Faras (2015)
The purpose of study is to identify the relationship between office environment and job satisfaction, to identify the type of office environment that influence job satisfaction among employees; to determine the significant difference in the average score of employees satisfaction among male and female respondents; and to investigate the relationship between office environment and job satisfaction among employees. The method was used a questionnaire for measuring office environment characteristics have developed. The employees population used in this study was limited to office workers in MAIK. Of the 140 completed questionnaires, 117 were analyzed for this study. The finding that was found such the type of office environment that most influence job satisfaction among employees at MAIK is furniture. By using independent sample t-test, there is a significant difference of job satisfaction between male and female respondents. However, there was a positive significant relationship between office environment and job satisfaction among employees at MAIK. The conclusion was overall about the investigation relationship between office environment and job satisfaction according to finding of the research got from the questionnaire that distributed. The office environment, office layout and colour has positive relationship with job satisfaction, however furniture and lighting has no relationship. For recommendation it was recommended that the suitable office environments that need to be applying at MAIK to increase job satisfaction among employees and the way that organization should implement to increase job satisfaction. In addition, recommend for future research such as used large number of correspondence, providing enough time, and reduce the number of questions.